Analysis on the Principles of Congestion Charging Policy and Study on the Decision-Making Model. (2016) - Liu, Yue-jun; Sun, Ming-Zheng; Zhou, Ling; Lu, Lu
Abstract: Transportation is an important safeguard for the running and development of a city. While, on the one hand, contribute to the soar and scale expansion of urban economy, urban transportation dominated by small vehicles, on the other hand, triggered various urban problems with respect to congestion, energy consumption and environment protection. Although demand-driven transportation development strategy has proved to effectively relieve congestion problems in urban transportation for a certain period of time, such strategy also led to an even swift inflation of traffic demand and thus it is not a thorough solution to the problem of supply and demand imbalance in urban transportation. Therefore, policies concerning the management of the demand of urban transportation represented by congestion charging policy gradually enter into the sight of decision makers of urban transportation and become an effective measure for first-tier cities in China to relieve congestion and improve air quality.